RURAL ECONOMIC EMPOWERMENT THROUGH AGRIBUSINESS DEVELOPMENT: A REVIEW OF RECENT LITERATURE - Mahidin Fahmie; Sigit Sugiardi; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2024)
Rural economic empowerment through agribusiness development has become an important focus in efforts to improve community welfare and reduce economic disparities between urban and rural areas. The review in this study uses the literature method. The review shows that agribusiness development has the potential to increase farmers' income, create jobs, and drive local economic growth. However, to advance this, challenges such as limited access to capital and technology, as well as the need for more supportive policies, still need to be addressed. Thus, a holistic and collaborative approach involving various stakeholders is needed to maximise the positive impact of agribusiness-based economic empowerment initiatives in rural areas.